VALUE RELEVANCE OF SUSTAINABILITY REPORT: EVIDENCE FROM INDONESIA - Endiana, I Dewa Made; Suryandari, Ni Nyoman Ayu (Jurnal Akuntansi dan Keuangan Indonesia, 2021)
This present study aimed at providing empirical evidence of whether sustainability report has value relevance for investors in buying or selling shares and affects firm value. This study used two research models. The first research model was used to examine the effect of book value and earnings on firm value. The second research model was used to examine the effect of sustainability report on firm value and define the value relevance of sustainability report. The samples of this study were 306 companies listed on the Indonesia Stock Exchange in 2017-2020. As a result, this study found that sustainability report is very useful information in making investment decisions. Investors do not only use short-term profits as a reference but also take sustainability report and long-term profits as a reference in making investment decisions.